The diversity of indigenous and potential bacteria as bioremediator of palm oil mill secondary effluent (POMSE) by metagenomics assessment - RIA KARNO; ENDANG ARISOESILANINGSIH; IRFAN MUSTAFA; DIAN SISWANTO (Society for Indonesian Biodiversity, 2024)
Abstract. Karno R, Arisoesilaningsih E, Mustafa I, Siswanto D. 2024. The diversity of indigenous and potential bacteria as bioremediator of palm oil mill secondary effluent (POMSE) by metagenomics assessment. Biodiversitas 25: 1194-1200. This study aimed to identify the indigenous bacteria for potential bioremediation agents of palm oil mill secondary effluent (POMSE). Samples were obtained from the secondary pond of palm oil mill treatment. The bacterial diversity on the POMSE water samples was revealed by Next Generation Sequencing (NGS) of 16S rRNA gene amplicons. The results showed that the high abundance of bacteria phylum was Pseudomonadota or Proteobacteria (50%), Bacillota (31%), Bacteroidota (5%), and Thermotogae (3%). A photosynthetic sulfur bacterium, Allochromatium humboldtianum, was the most abundant species detected in the POMSE, with more than 8% of the total Operational Taxonomic Unit (OTU) detected. It was followed by Allochromatium phaeobacterium (6%), Allochromatium sp. (6%), and Macromonas bipunctata (6%). Meanwhile, the level of physicochemical parameters in POMSE were relatively high for several main parameters of the quality standard of palm oil industry waste, such as Chemical Oxygen Demand (COD) and Biological Oxygen Demand (BOD). In contrast, oil and fat are low and meet the quality standards. The value of POMSE physicochemical parameters, including COD, BOD, and oil and fat, were 2,492.46, 852.96, and 6.20 mg/L, respectively. Metagenomic analysis showed that the bacterial community at POMSE was highly diverse. Nine dominant and codominant species found are Allochromatium humboldtianum, Allochromatium phaeobacterium, Allochromatium sp., Allochromatium vinosum, Macromonas bipunctata, Tepidibaculum saccharolyticum, Rhodocyclus purpureus, Comamonas nitrativorans, and Fervidobacterium riparium. Several indigenous bacterial species found in this research were bacteria that have potential as bioremediation agents for palm oil wastewater.